2009
DOI: 10.1111/j.1423-0410.2009.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

International collaborative study to evaluate candidate reference reagents to standardize haemagglutination testing for anti‐A and anti‐B in normal intravenous immunoglobulin products

Abstract: The establishment of preparations 07/306, 07/308 and 07/310 as reference reagents by the World Health Organization will facilitate global standardization of haemagglutination tests for anti-A and anti-B, ensure that such tests are sufficiently sensitive and specific, and facilitate identification of batches that exceed maximum recommended levels of anti-A and anti-B. The Commission of the European Pharmacopoeia and the United States Food and Drug Administration have adopted the same reference reagents includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Figure 6 depicts IVIG/SCIG binding profile to distinct biologically relevant glycans on the CFG glycan array version 5.1. IVIG/SCIG are known to contain IgG antibodies against blood group antigens and regulatory requirements are in place to control levels of these hemagglutinins to avoid adverse reactions in recipients (41). In our analysis, variable binding intensities of antibodies to blood group antigens were detected among the different preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 depicts IVIG/SCIG binding profile to distinct biologically relevant glycans on the CFG glycan array version 5.1. IVIG/SCIG are known to contain IgG antibodies against blood group antigens and regulatory requirements are in place to control levels of these hemagglutinins to avoid adverse reactions in recipients (41). In our analysis, variable binding intensities of antibodies to blood group antigens were detected among the different preparations.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed limit of 64 was suggested for the 5% preparations as a calculation based on the initial safe specification of 32 for a 3% preparation. The guidelines were reevaluated in the early 2000s as a result of profound inconsistency in titers generated by different facilities (18). In general, the inconsistencies are believed to result from the different testing methodologies in use (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…gel card vs. tube and the presence or absence of anti-human globulin), although it has also been shown that laboratories using the same methodologies often report discrepant titer results for the same preparations of IVIG (18). The National Institute for Biological Standards and Control (NIBSC) subsequently established a direct antiglobulin test (DAT) titer result as the industry standard by producing lyophilized ampules of positive control (anti-A of 32-64 and anti-B of 32) derived from donor plasma (18). At the time, these controls contained titers in excess of the commercially available IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…С целью устранения вариабельности результатов в методике ЕФ предусмотрено при-менение стандартных образцов. Положительный и отрицательный стандартные образцы представ-ляют собой раствор иммуноглобулина человека с содержанием гемагглютининов в диапазоне от 1:16 до 1:32 и менее 1:2 соответственно [29]. В случае если препарат ИГЧВВ содержит гемаг-глютинины более, чем в положительном стан-дартном образце, проводят еще одно опреде-ление с использованием стандартного образца лимита содержания гемагглютининов.…”
Section: методы оценки содержания анти-а-и анти-в-гемагглютининов в пunclassified